The Use of Specific Serological Biomarkers to Detect CaniLeish Vaccination in Dogs - Lima, Carla; Santarém, Nuno; Nieto, Javier; Moreno, Javier; Carrillo, Eugenia; Bartholomeu, Daniella Castanheira; Bueno, Lilian Lacerda; Fujiwara, Ricardo; Amorim, Célia; Cordeiro-da-Silva, Anabela (Frontiers in Veterinary Science, 2019)
Canine leishmaniosis (CanL) prevention in the Mediterranean basin is considered essential to stop human zoonotic visceral leishmaniasis. In this context, vaccination of dogs is expected to have a significant impact in disease control. CaniLeish® (Virbac Animal Health) is one of a few CanL vaccines that are at this moment licensed in Europe. This vaccine contains purified excreted-secreted proteins of Leishmania having several antigens/immunogens with potential to influence serological response. Therefore, it is important to know if CaniLeish vaccination increased the diagnostic challenges associated with conventional serology, limiting the value of some antigens. To address this 20 dogs from a cohort of 35 healthy dogs that were vaccinated, maintained indoor for one month and then returned to their natural domiciles for two years. After this period, they were re-called to evaluate their clinical/parasitological condition and assess the evolution of seroreactivity against different antigens: soluble promastigote Leishmania antigens (SPLA), recombinant protein Leishmania infantum cytosolic tryparedoxin, recombinant protein K39 (rK39), recombinant protein K28 and recombinant protein KDDR using ELISA. Two years after vaccination all vaccinated non-infected animals were seropositive for SPLA. For the other antigens the serological profile was indistinguishable from non-infected animals. Moreover, vaccinated animals presented a characteristic relative serological profile, with higher normalized serological response to SPLA than rK39. This fact enabled to distinguish with sensitivity 92.3% and specificity 95.4%, vaccinated non-infected dogs from infected and non-infected dogs. Ultimately, relative serological profile enabled the detection healthy vaccinated animals enabling more accurate serological surveys.